(untitled) (Scientific journal of the Fergana State University, 2023)
In this work, a method for the efficient synthesis of N, Nʹ-hexamethylene-bis - [(2,4,6-tribromophenoxy) -carbamate] is proposed, its chemical properties are studied, and its biostimulating activity is determined. In the experiments, varieties "Uzbekistan-740", tomatoes of the "Temp" variety and medium-staple cotton of the "C-6524" variety were used. The preparations were dissolved in DMF and used by pre-sowing seed soaking for 18-20 hours. Concentrations of 0.1% were used; 0.01% and 0.001%. The repetition of experiments is 4-fold. The counts were carried out by measuring the length of the stem and root of 10-day-old cotton seedlings. It was noted that all preparations tend to stimulate the growth of the root system of young seedlings, both vegetable crops and cotton.